Diaphyseal and Metaphyseal Modeling Defects—Clinical Findings and Identification of WRAP53 Deficiency in Craniometadiaphyseal Dysplasia - Hao, Yun; Wang, Xiao-Lin; Xiao, Jun; Jiao, Chun-Lei; Meng, Xin-Yao; Guo, Jia-Chao; Shao, Jing-Fan; Feng, Jie-Xiong; He, Jin-Peng (Frontiers in Genetics, 2021)
Background: Diaphyseal and metaphyseal modeling defects lead to severe changes in bone mass and shape of cortical bones which is a common feature in osteoporosis that linked to nonvertebral fractures. Original mechanism of diaphyseal and metaphyseal modeling defects has proved elusive. Studying rare syndromes can elucidate mechanisms of common disorders and identify potential therapeutic targets. Methods: We evaluated a family pedigree with craniometadiaphyseal dysplasia(CRMDD, OMIM 269300), a genetic disorder that is characterized by cortical-bone thinning, limb deformity, and absent of normal metaphyseal flaring and diaphyseal constriction. Systemic radiographic examination and serum hormone test were made for this rare disease. One patient and her two normal parents were examined by means of whole exome sequencing(WES) to identify the candidate pathogenic gene, and ruled out of Mucopolysaccharidosis and Prader-Willi Syndrome by means of Sanger sequencing. Results: There are several marked radiographic characteristics: (1) bullet shaped phalanges, (2) pointed chin shaped, long and narrow pelvic inlet, absent of supra-acetabular constriction, (3) round rod shaped long tubular bones, (4) prominent aiploic mastoid, (5) bending shaped limb, genua varus and genu varum, (6) congenital dislocation of elbow. Here we did not find any wormian bones. And there are several typical clinical characteristics: (1) macrocephaly and wide jaw, (2) Avatar elf shaped ears, pointed and protruding ears, (3) hypertrophy of limbs, (4) flat feet and giant hand phenomenon, (5) nail dystrophy, (6) limb deformity, (7) high arched palate, (8) superficial haemangiomas, (9) tall stature and intellectual disability. In this patient, we found biallelic frameshift deletion mutations in WRAP53. And those two muations were transmitted from her parents respectively. Conclusions: We describe her clinical and radiological findings and presented a new subtype without wormian bones and with a tall stature. Our study showed that craniometadiaphyseal dysplasia was caused by a deficiency of WRAP53 with autosomal recessive inheritance.